Why Employees Quit Their Jobs - Dolot, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article examines the issue of why employees leave their companies, focusing on four main reasons. The last of the four reasons is rooted in the organisation itself. Secondary research concernig the reasons for which employees leave their organisation was reviewed. It covers the costs organisations bear when employees leave and surveys the subject literature and also presents the results of research the author conducted in cooperation with ATERIMA. The article concludes with suggestions for practical actions intended to decrease employee turnover.